EFFECTS OF BIOLOGICAL AGE AND AGING RATES ON THE EXPRESSION OF RISK FACTORS IN PATIENTS WITH ARTERIAL HYPERTENSION AND TYPE 2 DIABETES MELLITUS - V.D. Nemtsova (Проблеми екології та медицини)
Objective: biological age has been given a large role in determining the significance and contribution to the general concept of risk factors in recent years. The relevance of determining the rate of aging is also due to the fact that the rate of aging may have a real prognostic value for assessing the health of both an individual and groups exposed to one or another risk factor. The aim of the present paper was to study the biological age, to assess the rate of aging in persons with high cardiovascular risk (CVR), as well as to carry out search for possible correlations of age-related indices of aging and some risk factors. Methods: During 2016-2018, 96 patients (42 men and 54 women), whose mean age was 62.66 ± 4.21 years, with AH stage II (disease duration of 10.2 ± 3.7 years) and DM2T, disease duration of 4.1 ± 2.4 years) were included in the study. The biological age and rate of aging was investigated by the method of V.P. Voitenko et al. Results: Physiological aging was observed in 9.38% (9/96) patients, in 31.25% (30/96) there was a delayed rate of aging, in 59.38% (57/96) - an accelerated rate of aging (ARA). ARA was characterized by a more pronounced body mass index, fasting blood glucose level, insulin resistance degree. In men, ARA was observed 2 times more frequently than in women. The most significant correlations between the indices characterizing the biological age and the rate of aging were recorded with systolic, diastolic and pulse arterial pressure. Conclusion: Thus, the complex of anthropometric and metabolic disorders can act as an initiating syndrome of accelerated aging, thereby aggravating the existing cardiovascular risk.